أزمة الشاعر المخضرم (في صدر الإسلام) - أحمد عدنان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
يحاول هذا البحث المتواضع أنْ يبيّن أنَّ عجز الشاعر المخضرم عن إنتاج شعر "إسلامي" رفيع المستوى، لم يكن مرتبطا بضعف موهبته الشعرية، أو بموقف الإسلام من الشعر، أو بانشغال العرب عن هذا الفن القولي الأصيل والمهمّ، بل كان ناتجا عن "أزمة" عانى منها الشاعر، شكلتها مجموعة الظروف التي أحاطت به. ولذلك فهو يرى أنه من الإنصاف أن يقف عند تلك الظروف، أو عند أكثرها تأثيرا، قبل أن يحكم للشاعر، أو عليه، من خلال شعره، أو من خلال ما وصل إلينا من شعره، بعبارة أدق. والشاعر المخضرم الذي يعني البحث، هو الشاعر الذي انشغل بحركة بناء الدولة الجديدة. أما الذي انصرف إلى حياته الخاصة، بعيدا عن مجريات الأحداث المتسارعة، فلا يدخل في إطاره. This paper attempts to highlight that the pre-and-post Islamic poet’s inability to produce ’Islamic’ poetry of high quality has not been ascribed to the weakness of his poetic talent nor to the position of Islam on poetry nor to Arabs breaking away from this significant discourse technique, but has rather been the outcome of a ’crisis’ the poet has gone through owing to a host of circumstances. Thus, he considers it viable to take these circumstances into account before vouching for the poet or against him in the light of his poetry or what we have obtained from it. The pre-and-post Islamic poet at issue here is the one involved in building the new state, whereas the one preoccupied with his private life, away from the run of spiralling events, falls out of the scope of this study.